Probiotic Lactobacillus acidophilus Strain INMIA 9602 Er 317/402 Administration Reduces the Numbers of Candida albicans and Abundance of Enterobacteria in the Gut Microbiota of Familial Mediterranean Fever Patients - Pepoyan, Astghik; Balayan, Marine; Manvelyan, Anahit; Galstyan, Lilit; Pepoyan, Sofi; Petrosyan, Susanna; Tsaturyan, Vardan; Kamiya, Shigeru; Torok, Tamas; Chikindas, Michael (Frontiers in Immunology, 2018)
Intestinal microorganisms play a crucial role in health and disease. The disruption of host –microbiota homeostasis has been reported to occur not only during disease development, but also as a result of medication. Familial Mediterranean fever (FMF) is an inflammatory genetic disease characterized by elevated systemic reactivity against the commensal gut microbiota and high levels of Candida albicans in the gut. This study’s major objective was to investigate the effects of commercial probiotic Narine on the relative abundance of gut bacteria (specifically, enterobacteria, lactobacilli, Staphylococcus aureus, and enterococci) of Candida albicans carrier and non-carrier FMF patients in remission. Our main finding indicates that the probiotic reduces numbers of C. albicans and abundance of enterobacteria in male and female patients of C. albicans carriers and non-carriers. It has pivotal effect on Enterococcus faecalis: increase in male non-carriers and decrease in female ones regardless of C. albicans status. No effect was seen for Lactobacillus and S. aureus. Our data suggest that M694V/V726A pyrin inflammasome mutations leading to FMF disease may contribute to gender specific differences in microbial community structure in FMF patients. The study’s secondary objective was to elucidate the gender-specific differences in the gut’s microbial community of FMF patients. The tendency was detected for higher counts of enterobacteria in female FMF subjects. However, the small number of patients of these groups preclude from conclusive statements, pointing at the need for additional investigations with appropriate for statistical analysis groups of subjects involved in the study.